The Students' Responses on Learning English Phonology Deploying Scaffolding: How does This Technique Support Higher Linguistics Stages? - Nurhayati, Dwi Astuti Wahyu (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2022)
The indicated research aimed to identify pupils’ reactions to the deploying scaffolding technique to learn English phonology. In this research, the data were assembled for 5 months, starting from February to June 2022, and they were gained through observation and distributing questionnaires by individual and group assessment. It involved 48 Indonesian college students in the second semester who were majoring in English and joining English phonology classes as well. The students and lecturers conducted demonstrative school room reciprocal action in English interaction phases in UIN SATU Tulungagung, East Java, Indonesia. The inputs could be figured out by adopting a qualitative way. From the results, it can be discovered that the implementation of scaffolding techniques in understanding English phonology influenced students deeply. The result showed that some students’ perspectives included: the students ‘handling difficulties in conducting teamwork for scaffolding technique, students’ ability in understanding English phonology, and student’s attitudes towards the implementation of scaffolding during the learning process.